Modeling of transport phenomena during solidification of binary systems - Furmański, Piotr (Computer Assisted Methods in Engineering and Science, 2023)
The macroscopic equations describing the process of solidification in binary systems are usually introduced via the volume averaging technique. A different approach to obtain these equations, based on the ensemble averaging technique, is proposed in the paper. This technique was used to derive energy and solute conservation equations and the basic constitutive relations appearing in the macroscopic description of the solidification phenomena occurring in the mushy region. In general these relations are non-local and account for non-equilibrium processes. Problem of thermodynamic equilibrium (thermal and chemical) is also discussed. Formulae for enthalpy and porosity of the mushy zone, in the latter case, are given.